Private Sector-led Urban Development Projects. Management, Partnerships and Effects in the Netherlands and the UK - Heurkens, Erwin (Architecture and the Built Environment, 2012)
Central to this research lays the concept of private sector-led urban development projects (Heurkens, 2010). Such projects involve project developers taking a leading role and local authorities adopting a facilitating role, in managing the development of an urban area, based on a clear public-private role division. Such a development strategy is quite common in Anglo-Saxon urban development practices, but is less known in Continental European practices. Nonetheless, since the beginning of the millennium such a development strategy also occurred in the Netherlands in the form of ‘concessions’. However, remarkably little empirical knowledge is available about how public and private actors collaborate on and manage private sector-led urban development projects. Moreover, it remains unclear what the effects of such projects are. This dissertation provides an understanding of the various characteristics of private sector-led urban development projects by conducting empirical case study research in the institutional contexts of the Netherlands and the UK. The research provides an answer to the following research question: What can we learn from private sector-led urban development projects in the Netherlands and UK in terms of the collaborative and managerial roles of public and private actors, and the effects of their (inter)actions? Indications for a market-oriented Dutch urban development practice Urban development practice in the Netherlands has been subject to changes pointing towards more private sector involvement in the built environment in the past decades. Although the current economic recession might indicate otherwise, there are several motives that indicate a continuation of private sector involvement and a private leadership role in Dutch urban development projects in the future. First, a shift towards more market-oriented development practice is the result of an evolutionary process of increased ‘neoliberalization’ and the adoption of Anglo-Saxon principles in Dutch society. Despite its Rhineland roots with a focus on welfare provision, in the Netherlands several neoliberal principles (privatization, decentralization, deregulation) have been adopted by government and incorporated in the management of organizations (Bakker et al., 2005). Hence, market institutionalization on the one hand, and rising civic emancipation on the other, in current Western societies prevents a return towards hierarchical governance. Second, the result of such changes is the emergence of a market-oriented type of planning practice based on the concept of ‘development planning’. Public-Private Partnerships and the ‘forward integration’ of market parties (De Zeeuw, 2007) enforce the role of market actors. In historical perspective, Boelens et al. (2006) argue that Dutch spatial planning always has been characterized by public-private collaborations in which governments facilitated private and civic entrepreneurship. Therefore, post-war public-led spatial planning with necessary government intervention was a ‘temporary hiccup’, an exception to the rule. Third, the European Commission expresses concerns about the hybrid role of public actors in Dutch institutionalized PPP joint ventures. EU legislation opts for formal public-private role divisions in realizing urban projects based on Anglo-Saxon law that comply with the legislative tendering principles of competition, transparency, equality, and public legitimacy. Fourth, experiences with joint ventures in the Netherlands are less positive as often is advocated. Such institutionalized public-private entities have seldom generated the assumed added value, caused by misconceptions about the objectives of both partners grounded in incompatible value systems. This results in contra-productive levels of distrust, time-consuming partnership formations, lack of transparency, and compromising decision-making processes (Teisman & Klijn, 2002), providing a need for other forms of collaboration. Finally, current financial retrenchments in the public sector and debates about the possible abundance of Dutch active land development policies point towards a lean and mean government that moves away from risk-bearing participation and investment in urban projects and leaves this to the market. Importantly, Van der Krabben (2011b) argues that the Dutch active public land development policies can be considered as an international exception, and advocates for facilitating land development policies. In this light, it becomes highly relevant to study private sector-led urban development as a future Dutch urban development strategy. Integrative urban management approach This research is rooted in the research school of Urban Area Development within the Department of Real Estate and Housing at the Faculty of Architecture (Delft University of Technology). It is a relatively young academic domain which views urban development most profoundly as a complex management assignment (Bruil et al., 2004; Franzen et al., 2011). This academic school uses an integrative perspective with a strong practice-orientation and carries out solution-oriented design research. Here, the integration involves bridging various actor interests, spatial functions, spatial scales, academic domains, knowledge and skills, development goals, and links process with content aspects. Such a perspective does justice to complex societal processes. Therefore it provides a fruitful ground for studying urban development aimed at developing conceptual knowledge and product for science and practice. Such integrative perspective and practice-orientation forms the basis of this research and has been applied in the following manner. In order to create an understanding of the roles of public and private actors in private sector-led urban development, this research takes a management perspective based on an integrative management approach. This involves viewing management more broadly as ‘any type of direct influencing’ urban development projects, and therefore aims at bridging often separated management theories (Osborne, 2000a). Hence, an integrative management approach assists in both understanding urban development practices and projects and constructing useful conceptual tools for practitioners and academics. Integrative approaches attempt to combine a number of different elements into a more holistic management approach (Black & Porter, 2000). Importantly, it does not view the management of projects in isolation but in its entire complexity and dynamics. Therefore, our management approach combines two integrative management theories; the open systems theory (De Leeuw, 2002) and contingency theory. The former provides opportunities to study the management of a project in a structured manner. The latter emphasizes that there is no universally effective way of managing and recognizes the importance of contextual circumstances. Hence, an integrative management approach favors incorporating theories from multiple academic domains such as political science, economics, law, business administration, and organizational and management concepts. Hence, it moves away from the classical academic division between planning theory and property theory, and organization and management theories. It positions itself in between such academic domains, and aims at bridging theoretical viewpoints by following the concept of planning ánd markets (Alexander, 2001) rather than concepts such as ‘planning versus markets’, public versus private sector, and organization versus management. Also, such an integrative view values the complexity and dynamics of empirical urban development practices. More specifically, this research studies urban development projects as object, as urban areas are the focus point of spatial intervention and public-private interaction (Daamen, 2010), and thus collaboration and management. Here, public planning processes and private development processes merge with each other. Thus, our research continues to build upon the importance of studying and reflecting on empirical practices and projects (e.g. Healey, 2006). In addition to these authors, this research does so by using meaningful integrative concepts that reflect empirical realities of urban projects. Thereby, this research serves to bridge management sciences with management practices (Van Aken, 2004; Mintzberg, 2010) through iterative processes of reflecting on science and practice. Moreover, the integrative management approach applied in this research assists in filling an academic gap, namely the lack of management knowledge about public-private interaction in urban development projects. Despite the vast amount of literature on the governance of planning practices (e.g. DiGaetano & Strom, 2003), and Public-Private Partnerships (e.g. Osborne, 2000b), remarkable little knowledge exists about what shifting public-private relationships mean for day-to-day management by public and private actors in development projects. Hence, here we follow the main argument made by public administration scholar Klijn (2008) who claims that it is such direct actor influence that brings about the most significant change to the built environment. An integrative urban management model (see Figure 2.3) based on the open systems approach has been constructed which forms a conceptual representation of empirical private sectorled urban development projects. This model serves as an analytical tool to comprehend the complexity of managing such projects. In this research, several theoretical insights about publicprivate relations and roles are used to understand different contextual and organizational factors that affect the management of private sector-led urban development projects. Hence, a project context exists within different often country-specific institutional environments (e.g. the Netherlands and UK). In this research, contextual aspects that to a degree determine the way public and private actors inter-orga